Pre-school Teachers' Stereotypes and Self-Efficacy are Linked to Perceptions of Behavior Problems in Newly Arrived Refugee Children - Chwastek, Sandy; Leyendecker, Birgit; Heithausen, Anna; Ballero Reque, Cristina; Busch, Julian (Frontiers in Psychiatry, 2021)
Introduction. Since 2015, increased numbers of refugee families have been arriving in Germany. With the transition of newly arrived refugee children into preschools, teachers’ professional competence for teaching those children and adapting to their socio-emotional needs has become increasingly important. Previous research demonstrated that teachers’ stereotypes and cultural beliefs were related to their self-efficacy and enthusiasm when teaching immigrant children. The aims of this study were A) to expand those findings by investigating the links between preschool teachers’ stereotypes, multicultural beliefs, self-efficacy, and enthusiasm when teaching newly arrived refugee children, and B) to investigate whether teacher’ professional competence was linked to their perceptions of newly arrived refugee children’s behavior problems. Method. We analyzed responses to a cross-sectional self-report survey from N = 147 German preschool teachers. Teachers reported on their negative stereotypes towards refugee children, multicultural beliefs, self-efficacy, and enthusiasm for teaching refugee children, and completed the Strengths and Difficulties Questionnaire (SDQ) for a selected refugee child from their preschool group. We used regression modeling. First, we related teachers’ negative stereotypes and multicultural beliefs to their self-efficacy and enthusiasm for teaching refugee children. Second, we examined the links between teachers’ beliefs, values, and motivational orientations to their ratings on the SDQ subscales. Third, we linked demographic data of teachers and children to teachers’ professional competence and SDQ ratings. Results. Teachers with more negative stereotypes towards newly arrived refugee children and less agreement with multicultural beliefs reported lower self-efficacy and enthusiasm for teaching newly arrived refugee children. Teachers with more negative stereotypes perceived more hyperactivity/inattention and total difficulties. Teachers with higher self-efficacy perceived less hyperactivity/inattention, less total difficulties, and more prosocial behavior. Additionally, teachers that were more experienced with refugee children reported more negative stereotypes and higher agreement with multicultural beliefs. Teachers having more overall work experience perceived more total difficulties. Boys were perceived to display more externalizing behavior problems, less prosocial behavior, and more total difficulties. Older children were perceived as displaying more prosocial behavior. Discussion. Our findings suggest that preschool teachers’ stereotypes and self-efficacy might be related to perception biases concerning newly arrived refugee children’s externalizing behavior problems.